2019
DOI: 10.1186/s12891-019-2802-y
|View full text |Cite
|
Sign up to set email alerts
|

The dysplastic trochlear sulcus due to the insufficient patellar stress in growing rats

Abstract: Background Developmental factors were assumed to be the key factors that influenced the morphology of femoral trochlea. This study investigated the effects of insufficient patellar stress after birth on the morphological development of the femoral trochlea. Effects of insufficient patellar stress on femoral trochlea were investigated using surgical induced patellectomy and patellar dislocation in growing rat model. Methods In this study, two experimental groups and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 41 publications
6
38
0
Order By: Relevance
“…Notably, our previous study con rmed that TD can lead to cartilage degeneration [24,25]. In the present study, we found that, with increasing age, cartilage morphology changed in the rat TD model: its surface became rough, vertical cracks appeared, and articular chondrocytes aggregated.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Notably, our previous study con rmed that TD can lead to cartilage degeneration [24,25]. In the present study, we found that, with increasing age, cartilage morphology changed in the rat TD model: its surface became rough, vertical cracks appeared, and articular chondrocytes aggregated.…”
Section: Discussionsupporting
confidence: 60%
“…An incision was then made along the midline of the skin; the skin and subcutaneous tissue were separated, exposing the joint capsule through the medial approach to the knee. The procedure to induce patellar instability was performed as described in our previous studies [24,25]. Speci cally, a 0.5-cm longitudinal incision was made along the patella at the medial capsule and retinaculum.…”
Section: Surgical Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Incising along the midline of the skin, separating the skin and subcutaneous tissue subsequently, exposing the joint capsule via the medial approach of the knee. Similar surgeries of patellar instability have been informed in our earlier researches [24,25]. In this research, along the patellar, making a 0.5 cm longitudinal incision at the medial capsule and retinaculum.…”
Section: Surgical Techniquementioning
confidence: 94%
“…We all know that transforming growth factor β1 (TGFβ1) plays an significant part in the development of chondrocytes, it has a good ability to regulate the extracellular matrix (ECM) biosynthesis, and it is one of the regulators of cartilage metabolic activity that we have extensively studied [23]. Previous studies have shown that TD can cause degeneration of articular cartilage [24,25]. However, the molecular mechanism of TD induced cartilage degeneration is uncertain until now.…”
Section: Introductionmentioning
confidence: 99%